The perception of visually impaired students in relation to the schooling process - Montilha, Rita de Cassia Ietto; Temporini, Edméa Rita; Nobre, Maria Inês Rubo de Souza; Gasparetto, Maria Elisabete Rodrigues Freire; José, Newton Kara (Paidéia (Ribeirão Preto), 2009)
The inclusion of people with visual impairment in the school system demand professionals to know these students' perceptions regarding their limitations and possibilities. Characteristics and perceptions of students with visual impairment related to their process of rehabilitation were identified in this study. This cross-sectional and descriptive study was carried out with 12-year students included in the public school system of a city in the state of São Paulo, Brazil. A questionnaire was applied through interviews. A population of 26 students, 46.2% with low vision and 53.8% with blindness, with an average age of 17.1 years was obtained. School failure was reported by 73.1%. Reading didactic books stood out among difficulties faced due to blindness and visualization of the blackboard stood out among difficulties due to low vision. Education level was considered low in relation to the average age. Coherent perceptions related to the school inclusion problem were evidenced.